Evaluation of Ultrasonic Velocity in Binary Liquid Mixtures - TAWAKYA SINGH, RAM; KUMAR THAKUR, PRAVEEN (Asian Journal of Chemistry, 2010)
The experimental ultrasonic velocity of binary liquid mixtures is compared with theoretical values based on Nomto's relation, Van Deal and Vangeel additive mixture relations. An attempt has been made to explain the positive as well as negative excess values obtained in three types of mixtures studied.